Recent Insights into the Implication of Nitric Oxide in Osteoblast Differentiation and Proliferation during Bone Development - Marta Saura; Carlos Tarin; Carlos Zaragoza (The Scientific World Journal)
Bone tissue renovation is a dynamic event in which osteoblasts and osteoclasts are responsible for the turnover between bone formation and bone resorption, respectively. During bone development, extracellular matrix remodeling is required for osteoblast differentiation and the process is largely mediated by the proteolytic activity of extracellular matrix metalloproteinases (MMPs), which play a fundamental role in osteoblast migration, unmineralized matrix degradation, and cell invasion. The recent advances towards investigation in osteogenesis have provided significant information about the transcriptional regulation of several genes, including MMPs, by the expression of crucial transcription factors like NFAT, ATF4, osterix, TAZ, and Cbfa-1–responsive elements. Evidence from gene knock-out studies have shown that bone formation is, at least in part, mediated by nitric oxide (NO), since mice deficient in endothelial nitric oxide synthase (eNOS) and mice deficient in the eNOS downstream effector (cGMP)-dependent protein kinase (PKG) show bone abnormalities, while inducible NOS (iNOS) null mice also show imbalances in bone osteogenesis and abnormalities in bone healing. Recently, in vitro data showed that Cbfa-1 and the MAPK pathways were crucial for osteoblastic cell differentiation, and NO was found to play a significant role. This article sheds light on some of the mechanisms that may influence NO-mediated actions in bone development.